2019
DOI: 10.1186/s12989-019-0321-5
|View full text |Cite
|
Sign up to set email alerts
|

An in-depth multi-omics analysis in RLE-6TN rat alveolar epithelial cells allows for nanomaterial categorization

Abstract: BackgroundNanomaterials (NMs) can be fine-tuned in their properties resulting in a high number of variants, each requiring a thorough safety assessment. Grouping and categorization approaches that would reduce the amount of testing are in principle existing for NMs but are still mostly conceptual. One drawback is the limited mechanistic understanding of NM toxicity. Thus, we conducted a multi-omics in vitro study in RLE-6TN rat alveolar epithelial cells involving 12 NMs covering different materials and includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 52 publications
(78 reference statements)
8
48
0
Order By: Relevance
“…This is in accordance with the literature, where it has been shown that SiO2_15_Unmod is "active" in vitro [38] and in vivo [25,73]. Importantly, SiO2_15_Amino was classi ed to be "passive" based on all conducted studies, which has been described before as well [11,25,38]. This illustrates that the used surface modi cation can in uence the effects, since the only difference between SiO2_15_Unmod and SiO2_15_Amino are amino groups on the surface of latter, which is in accordance to the literature [73].…”
Section: Comparison Of In Vivo and In Vitro Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…This is in accordance with the literature, where it has been shown that SiO2_15_Unmod is "active" in vitro [38] and in vivo [25,73]. Importantly, SiO2_15_Amino was classi ed to be "passive" based on all conducted studies, which has been described before as well [11,25,38]. This illustrates that the used surface modi cation can in uence the effects, since the only difference between SiO2_15_Unmod and SiO2_15_Amino are amino groups on the surface of latter, which is in accordance to the literature [73].…”
Section: Comparison Of In Vivo and In Vitro Resultssupporting
confidence: 91%
“…SiO2_15_Amino. Overall, the NM treatment of type II cells led to increased abundances of proteins and metabolites that are part of the GSH/GSSG signaling, thus indicating an increased production of GSH, especially in case of SiO2_40, SiO2_7, and TiO2_NM105, con rming that not only SiO2_40 and SiO2_7 are "active" NMs but also TiO2_NM105, which is consistent with our previous study [11].…”
Section: Gsh/gssg Signalingsupporting
confidence: 91%
See 3 more Smart Citations